Pertença religiosa e atividades de promoção humana em Muribeca dos Guararapes. - Abreu, Ijaciara Barros de (2009)
In the past, the suburb from the Jaboatão dos Guararapes’ city, Muribeca dos Guararapes had a great economic trade in the state due to its large sugar production. Now, it has pointed as a violent area and with a limited population by innumerable social and economic need. The quarter is divided onto defined and self-dynamical areas. It also shelters many workers from the Solid Residues Center of Muribeca. In despite of all its matters that this people have been living on situations like those workers live. We have observed through the twenty-five years of teaching there. It is noticed that there are persons taking to themselves the responsibility to do something that may minimize the necessity and to provide better conditions and life expectation by plans and contributions helped by religious thoughts shown from many religious denominations. The people watched are detained with charisma, expressed on their social care they do, besides it has not always been accredited by their neighbors. Releasing this work from those people is a way to identify the unrecognized values from people who wants, by they small part, to change their reality